2001
DOI: 10.1200/jco.2001.19.8.2282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Capecitabine Versus Intravenous Fluorouracil Plus Leucovorin as First-Line Treatment in 605 Patients With Metastatic Colorectal Cancer: Results of a Randomized Phase III Study

Abstract: Oral capecitabine was more active than 5-FU/LV in the induction of objective tumor responses. Time to disease progression and survival were at least equivalent for capecitabine compared with the 5-FU/LV arm. Capecitabine also demonstrated clinically meaningful benefits over bolus 5-FU/LV in terms of tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
529
4
17

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,044 publications
(576 citation statements)
references
References 38 publications
14
529
4
17
Order By: Relevance
“…These trials demonstrated that capecitabine showed increasing efficacy in terms of response rate, equivalent time to progression and survival, and had a superior safety profile. 4,5,7 It is noteworthy that response rates were consistently higher for capecitabine than for 5-FU/LV in subgroups that included patients with liver metastasis (25% vs. 17%, respectively) and patients with lung metastasis (30% vs. 8%, respectively). 4 In our study, we found a strong anti-metastatic efficacy of capecitabine in the HT-29 cell rectal xenograft model wherein capecitabine showed low susceptibility in the xenograft itself.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These trials demonstrated that capecitabine showed increasing efficacy in terms of response rate, equivalent time to progression and survival, and had a superior safety profile. 4,5,7 It is noteworthy that response rates were consistently higher for capecitabine than for 5-FU/LV in subgroups that included patients with liver metastasis (25% vs. 17%, respectively) and patients with lung metastasis (30% vs. 8%, respectively). 4 In our study, we found a strong anti-metastatic efficacy of capecitabine in the HT-29 cell rectal xenograft model wherein capecitabine showed low susceptibility in the xenograft itself.…”
Section: Discussionmentioning
confidence: 94%
“…4 -6 Randomized clinical trials that compared capecitabine with parenteral 5-FU/leucovorin against metastatic colorectal cancer demonstrated that capecitabine provides at least equivalence, a favorable benefit-risk ratio and greater patient preference making it an acceptable replacement for 5-FU/leucovorin. 4,5,7 Our interest focused on the possibility of capecitabine usage in the prevention of metastasis. Neoadjuvant or adjuvant chemotherapy to inhibit spontaneous metastasis or suppress occult micrometastasis may reduce the incidence of postoperative distant metastasis and improve survival.…”
Section: Abstract: Capecitabine; Lymph Node Metastasis; Lung Metastamentioning
confidence: 99%
“…Capecitabine and UFT/folinic acid already proved to be as effective as intravenous bolus 5-FU/folinic acid regimens Hoff et al, 2001;Van Cutsem et al, 2001), achieving response rates of 18.9 -24.8 and 12%, respectively, with less toxicity than with the 5-FU regimens. S-1 will have to be compared to those products in randomised studies to determine which oral fluoropyrimidine achieves the best results and the least toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, there has been an increasing use of capecitabine monotherapy and capecitabine-based combination regimens in the treatment of mCRC, which has been due, in large part, to the convenience and increased patient preferences for oral chemotherapy [5054]. Randomized studies have shown that capecitabine-based treatments are associated with equal clinical efficacy and reduced toxicities when compared to infusional 5-FU regimens [5054].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%
“…Randomized studies have shown that capecitabine-based treatments are associated with equal clinical efficacy and reduced toxicities when compared to infusional 5-FU regimens [5054]. Finally, several pharmacoeconomic studies have demonstrated that capecitabine-based chemotherapy is associated with significant cost savings when compared to infusional 5-FU chemotherapy, and these economic benefits are seen for the adjuvant therapy setting as well as for the treatment of metastatic disease [5559].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%